Do demographic changes affect house prices?. (December 2019) - Gevorgyan, Kristine
Abstract: The paper tests the idea that major demographic shifts can affect housing prices. We first build an overlapping generation model and analytically solve for the equilibrium price of the asset. The model predicts that economies with a higher fraction of old people in the overall population have lower house prices. We empirically test this hypothesis using data on house prices and demographic variables from the Organization for Economic Co-operation and Development (OECD). We find that if population growth increases by one percentage point, house price growth increases by 1.4 percentage points.